Effectiveness of an Advanced Naloxone Training, Simulation, and Assessment of Second-Year Pharmacy Students - Jennifer Courtney; Eugene Kreys; Bryan Luu; Tiffany Kreys; Ruth Vinall; Vy Quang; Erika Titus-Lay (Pharmacy, 2022)
Background: Opioid overdoses continue to be one of the most urgent public health priorities. In 2020, reported overdose deaths in the United States reached a high of over 93,000 cases. As the COVID-19 pandemic and opioid crisis continues to be addressed, life-saving agents must be more widely accessible to those with a high overdose risk. An essential step to increasing access is to train student pharmacists to dispense naloxone. Once licensed, the number of personnel authorized to dispense naloxone can increase. Objectives: To design a training program to educate second-year pharmacy (P2) students on furnishing naloxone under a state protocol. Methods: A multi-phased curriculum-based naloxone training program was delivered to P2 students and included lecture-based education, team-based learning (TBL) applications, case-based scenarios, and summative assessments to improve student knowledge and confidence in furnishing naloxone. Students were surveyed on their knowledge and confidence with naloxone prior to training, after the in-class training and TBL applications and after three assessments. Assessments included simulated patient counseling, case-based scenarios, and proper dispensing of naloxone in a community pharmacy simulation lab. Results: A total of 185 student pharmacists completed the naloxone training program and 68 completed all three surveys. Average scores for naloxone assessments were 83% for the APPS lab patient case, 90.5% for the prescription label typed for the naloxone product, and 88.5% for patient counseling. Statistically significant increases in knowledge-based quiz-like scores (42.1% after training vs. 7.2% after assessment) and in the proportion of students affirmatively answering survey questions after training and assessment was observed. Conclusion: Multi-phase curriculum-based naloxone training program improved pharmacy student knowledge and confidence in furnishing naloxone under a state BOP protocol.